The Influence of Oncogenic RAS on Chemotherapy and Radiotherapy Resistance Through DNA Repair Pathways - Cáceres-Gutiérrez, Rodrigo E.; Alfaro-Mora, Yair; Andonegui, Marco A.; Díaz-Chávez, José; Herrera, Luis A. (Frontiers in Cell and Developmental Biology, 2022)
RAS oncogenes are chief tumorigenic drivers, and their mutation constitutes a universal predictor of poor outcome and treatment resistance. Despite more than 30 years of intensive research since the identification of the first RAS mutation, most attempts to therapeutically target RAS mutants have failed to reach the clinic. In fact, the first mutant RAS inhibitor, Sotorasib, was only approved by the FDA until 2021. However, since Sotorasib targets the KRAS G12C mutant with high specificity, relatively few patients will benefit from this therapy. On the other hand, indirect approaches to inhibit the RAS pathway have revealed very intricate cascades involving feedback loops impossible to overcome with currently available therapies. Some of these mechanisms play different roles along the multistep carcinogenic process. For instance, although mutant RAS increases replicative, metabolic and oxidative stress, adaptive responses alleviate these conditions to preserve cellular survival and avoid the onset of oncogene-induced senescence during tumorigenesis. The resulting rewiring of cellular mechanisms involves the DNA damage response and pathways associated with oxidative stress, which are co-opted by cancer cells to promote survival, proliferation, and chemo- and radioresistance. Nonetheless, these systems become so crucial to cancer cells that they can be exploited as specific tumor vulnerabilities. Here, we discuss key aspects of RAS biology and detail some of the mechanisms that mediate chemo- and radiotherapy resistance of mutant RAS cancers through the DNA repair pathways. We also discuss recent progress in therapeutic RAS targeting and propose future directions for the field.